Spacecraft disposal in quasi-geostationary orbit - Ashurov, А.Е. (Publishing House of the KarSU named after E.A. Buketov, 2018)
The results of simulation of the process of the disposal (post-mission disposal or disposal after failure as a result of emergency) of a spacecraft in quasi-geostationary orbit are given. The necessary impulses, fuel consumption for maneuvers, the required time for the raising the orbit to 300 km, changes in the major semi-axis and eccentricity of the orbit and the satellite's drift in longitude are calculated. The process of raising the orbit is considered as a result of successive starts of gas engines (GE) and corresponding changes in the indicated orbital parameters. The dependence of the satellite drift and longitude for different values of eccentricity is presented. It is shown that, within the maximum duration of the engine operation time of the GE, the duration of their individual starts does not significantly affect the final results of the disposal.
Keywords: Spacecraft; geostationary orbit; disposal; maneuvers; numerical simulations; orbit parameters